Pengaruh ServQual Terhadap EWOM Melalui Trust dan E-Satisfaction Online Merchant - Rahmi Yuliana; Rinwantin Rinwantin (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
This study aims to analyze and explore more deeply the concept of electronic word of mouth (eWOM) by examining the role of electronic service quality, with trust as an exogenous variable and electronic satisfaction as a mediating variable. The phenomenon of consumer behavior in the context of e-commerce continues to grow in line with the rapid increase in internet users. In Indonesia, internet users are projected to reach 72.8 million people, making the country the third-largest in internet penetration among ASEAN nations. This surge in internet usage has significantly influenced online shopping behavior, especially among digital-savvy consumers. However, this trend contrasts sharply with the declining performance of offline retail, as shopping centers are witnessing a drop in consumer visits. This decline is largely driven by three major factors: (1) shifting consumer preferences, (2) decreasing employment in physical retail sectors, and (3) a rapid rise in the number of online stores.The research utilizes primary data, collected from respondents who have made online purchases from two major marketplaces in Indonesia—Tokopedia and Lazada. The data were analyzed using the Smart PLS software to test the relationships between the variables. The results indicate that electronic service quality has a positive and significant effect on eWOM when mediated by trust. However, the direct effects of service quality and satisfaction on eWOM were found to be statistically insignificant. The findings suggest that building customer trust through enhanced service quality is a strategic priority for e-commerce platforms aiming to encourage consumers to share positive online recommendations.